2008
DOI: 10.1159/000166839
|View full text |Cite
|
Sign up to set email alerts
|

Misdiagnosis of Transient Ischemic Attacks in the Emergency Room

Abstract: Background: To determine a pattern of symptoms and/or risk factors that distinguishes transient ischemic attack (TIA) from nonischemic causes of transient neurologic attacks (NI-TNA). Methods: We reviewed demographic, clinical, and hospital data on 100 consecutive patients with transient focal neurologic episode(s) lasting less than 24 h and in whom the initial diagnosis was TIA. After inpatient evaluation and review, final diagnoses were made by two stroke neurologists. Using stepwise multivariable logistic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
118
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(132 citation statements)
references
References 38 publications
7
118
0
7
Order By: Relevance
“…[23][24][25] In our study, the discharge diagnosis of TIA agreed with the diagnosis after being seen in the neurovascular clinic in 86.4% of patients. Including or excluding these patients did not change our results.…”
Section: Discussionsupporting
confidence: 73%
“…[23][24][25] In our study, the discharge diagnosis of TIA agreed with the diagnosis after being seen in the neurovascular clinic in 86.4% of patients. Including or excluding these patients did not change our results.…”
Section: Discussionsupporting
confidence: 73%
“…Some investigators have reported a false diagnosis rate of up to 60% in one U.S. study of inpatients initially assessed by an emergency physician, including those with gradual onset and nonspecific neurological symptoms. 26 These results are not unexpected given the transient nature of the symptoms and the fact that many patients present at a time when their symptoms have already started to resolve. We believe that, given the specific nature of isolated aphasia, the subsequent stroke risk, and the explicit, prospective identification of neurological signs and symptoms as well as other elements of our study, the large majority of patients in our cohort had a TIA.…”
Section: Discussionmentioning
confidence: 88%
“…Studies have shown up to an 80% reduction in the risk of stroke after TIA with the early implementation of secondary stroke prevention strategies, 11,12 including revascularization of patients with symptomatic carotid artery stenosis, anticoagulation of patients with atrial fibrillation, treatment with antiplatelet agent(s), treatment with statins for most patients, management of hypertension, and lifestyle…”
Section: Imaging and Prognosismentioning
confidence: 99%